Convergence, Divergence and a Complex Interplay: Chile and the International and Transnational Anti-Corruption Campaign - Malte Gephart (German Institute of Global and Area Studies (GIGA), 2013)
Several anthropological scholars have argued from an ethnographic viewpoint that local understandings of corruption vary around the world. Others who have critically analyzed the international and transnational anti-corruption campaign (ITACC) have argued that the ITACC is capable of covering up these differences, which creates misunderstandings about the aims in the fight against corruption. This article combines and advances both arguments by applying a post-development perspective and argumentative discourse analysis (ADA) to explore the local anti-corruption discourse in Chile - a country that is considered a success case in Latin America. This exploration shows that Chile's anti-corruption activities are highly political and are deeply related to narratives in the country's transition to democracy. By relating local narratives back to the ITACC the article reveals a complex interplay between local (and competing) corruption narratives that, at the same time, partially form discourse coalitions with the ITACC.
Keywords: 300; corruption; anti-corruption; discourse analysis; narratives; Chile; Latin America; post development